2002
DOI: 10.1046/j.1365-313x.2002.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant RanGAPs are localized at the nuclear envelope in interphase and associated with microtubules in mitotic cells

Abstract: SummaryIn animals and yeast, the small GTP-binding protein Ran has multiple functions ± it is involved in mediating (i) the directional passage of proteins and RNA through the nuclear pores in interphase cells; and (ii) the formation of spindle asters, the polymerization of microtubules, and the re-assembly of the nuclear envelope in mitotic cells. Nucleotide binding of Ran is modulated by a series of accessory proteins. For instance, the hydrolysis of RanGTP requires stimulation by the RanGTPase protein RanGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 34 publications
4
74
0
Order By: Relevance
“…Judged by the resistance phenotypes of Rx1 targeted to the cytoplasm or the nucleus, Rx1 needs to be distributed among both compartments for full functionality. It is interesting to note that RanGAP2, which interacts with the CC domain of Rx1, has an almost exclusive cytoplasmic localization (Rose and Meier, 2001;Pay et al, 2002;Jeong et al, 2005;Sacco et al, 2007;Tameling and Baulcombe, 2007). Although silencing RanGAP2 in N. benthamiana compromised Rx1-mediated resistance (Tameling and Baulcombe, 2007) and overexpression of RanGAP2 caused the elicitor-independent activation of Rx1 CC-NB fragments (Sacco et al, 2007), the precise function of the RanGAP2 interaction with Rx1 is still unknown.…”
Section: Rx1 Is Activated In the Cytoplasmic Compartmentmentioning
confidence: 99%
“…Judged by the resistance phenotypes of Rx1 targeted to the cytoplasm or the nucleus, Rx1 needs to be distributed among both compartments for full functionality. It is interesting to note that RanGAP2, which interacts with the CC domain of Rx1, has an almost exclusive cytoplasmic localization (Rose and Meier, 2001;Pay et al, 2002;Jeong et al, 2005;Sacco et al, 2007;Tameling and Baulcombe, 2007). Although silencing RanGAP2 in N. benthamiana compromised Rx1-mediated resistance (Tameling and Baulcombe, 2007) and overexpression of RanGAP2 caused the elicitor-independent activation of Rx1 CC-NB fragments (Sacco et al, 2007), the precise function of the RanGAP2 interaction with Rx1 is still unknown.…”
Section: Rx1 Is Activated In the Cytoplasmic Compartmentmentioning
confidence: 99%
“…33,34 Plant RanGAP proteins are located on the nuclear envelope, mitotic spindles, phragmoplast and PPBs. 27,[35][36][37] Arabidopsis has 2 RanGAP proteins, AtRanGAP1 and AtRan-GAP2. 35 The plant RanGAPs have a unique N-terminal domain called WPP domain, 38 which is considered to be a target domain necessary for anchoring AtRanGAP1 to the nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%
“…27,[35][36][37] Arabidopsis has 2 RanGAP proteins, AtRanGAP1 and AtRan-GAP2. 35 The plant RanGAPs have a unique N-terminal domain called WPP domain, 38 which is considered to be a target domain necessary for anchoring AtRanGAP1 to the nuclear envelope. 37,39 Plant RanGAPs extracted from cells in mitotic stages co-assemble with MTs in vitro, whereas those extracted from interphase cells do not co-assemble.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of Ran in rice increases the proportion of cells in G2 phase (Wang et al 2006), indicating that Ran is involved in cell cycle progression. Arabidopsis RanGAP localizes to spindles as well as the late spindle midzone (the phragmoplast; (Pay et al 2002), while AtRanBP1 is localized to the cytoplasm where it maintains its conserved function as a co-activator that stimulates the hydrolysis of RanGTP (Kim and Roux 2003). A recent study in Arabidopsis (Xu et al 2008) showed that RanGAP further localizes to preprophase bands (PPBs), which are cortical rings of microtubules found in plant cells during late interphase and prophase (see below for discussion of the PPB).…”
mentioning
confidence: 99%